Legal Protection For Consumers In Digital Payments On Feeder Bus Service (Study At The Public Company In The Pakuan Transport Area, Bogor City) - Nursilawati, Nursilawati; Daming, Saharuddin; Fajri, Ibrahim (JURNAL MAHASISWA YUSTISI, 2024)
Implementing digital payments can increase public interest in using feeder bus services. However, on the other hand, the implementation of digital payments also raises several crucial problems that befall consumers related to the presence of a digital payment system organized by Perumda Transpakuan Bogor City. This research aims to find out how legal protection efforts for consumers are carried out by Perumda Transpakuan Bogor City in the Digital Payment System on Feeder Buses. This research uses a type of legal research that combines normative and empirical, namely taking an approach by first examining the existing laws and regulations. relevant to the problem being researched or looking at it from a normative legal aspect, then the experience in digital payments on feeder bus services is also studied. Legal Protection Efforts for Consumers by Perumda Transpakuan Bogor City in the Digital Payment System on Feeder Buses, including: Compliance with Regulations, Collaboration with Leading third party, Data security system, Verification and authentication system, Dispute resolution and refunds, Education and outreach, Regular audits and monitoring.